Building Information Technology Infrastructure for a Creative College - Nguyễn, Tùng Thanh; Phạm, Minh Nhật; Nguyễn, Thanh Hải (VNU Journal of Science: Social Sciences and Humanities; Vol 31 No 4, 2015)
In this report, we present some basic content needs of information technology infrastructure in the direction of a creative college, including improving technical facilities of the network infrastructure, strengthening infrastructure network engineering, bandwidth expansion, development of software systems, opening studio workshops, factory electronic materials, building shared resources such as e-learning system, the sources materials for research, laboratory systems and building shared integrated data center unification.